Protocol for a multisite, observational clinical study of the association between skin colour and pulse oximeter accuracy in children undergoing cardiac catheterisation (PACH study) - Elizabeth E Foglia; Halley Ruppel; Christopher P Bonafide; Liming Huang; Christopher J Petit; Meghan B Lane-Fall; Athar M Qureshi; Jeffery Feldman; Jennifer M Lynch; Anna Chien; Michelle Dunn; Michael L O’Byrne (BMJ Open)
Introduction Prospective, real-world clinical studies of the association between skin color and pulse oximeter (SpO2) accuracy in children are needed to address the limitations of previous research. Such studies are essential for generating evidence for clinicians, regulators and industry. This is the protocol for a multisite study funded by the National Heart, Lung, and Blood Institute (R01HL171313; 1 January 2024–31 December 2028).Methods and analysis In this pragmatic, observational study conducted in three large paediatric cardiac catheterisation centres in the USA, children undergoing cardiac catheterisation with directly measured arterial oxygen saturation will be prospectively enrolled. The outcome variable (SpO2 bias) is the difference between contemporaneous paired measurements of pulse oximetry (SpO2) and the standard reference comparator, arterial blood sample oxygen saturation (SaO2), obtained during the catheterisation procedure. The independent variable is an objective measure of skin colour obtained via spectrophotometry. Our primary analysis is a multivariable regression model testing the relationship between skin colour and SpO2 bias, after adjusting for covariates. We will also conduct a moderator analysis to identify factors that may affect the magnitude of the association. The target sample size is 584 participants.Ethics and dissemination This study was approved by the University of Pennsylvania Institutional Review Board (#854895) under expedited review. Study risks are minimal. Parental permission, and child assent when applicable, are obtained prior to enrolment. In accordance with the NIH Public Access Policy, publications associated with the study will be made publicly available through PubMed Central. The analytic dataset will be contributed to a repository for future use. In collaboration with a children’s hospital-based research family advisory council, interpretation and dissemination of the results for lay, clinical and scientific audiences will be considered.Trial registration number Although not a clinical trial, this observational study is registered on ClinicalTrials.gov (identifier: NCT06529575) for public awareness.